(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
In this paper I aim at retracing the editorial history of Nuova enciclopedia, a posthumous book by Alberto Savinio published by Adelphi in 1977 and reprinted in 2017. Rooted in archival survey, the essay focuses on the critical issues of the 1977 Edition, whose chief editors are not indicated. The overall problem this essay is concerned is how the text was edited, which is not possible to deduce in a clear and exhaustive way at the current state of research.